2017
DOI: 10.1111/1460-6984.12333
|View full text |Cite
|
Sign up to set email alerts
|

Semantic fluency in deaf children who use spoken and signed language in comparison with hearing peers

Abstract: BackgroundDeafness has an adverse impact on children's ability to acquire spoken languages. Signed languages offer a more accessible input for deaf children, but because the vast majority are born to hearing parents who do not sign, their early exposure to sign language is limited. Deaf children as a whole are therefore at high risk of language delays.AimsWe compared deaf and hearing children's performance on a semantic fluency task. Optimal performance on this task requires a systematic search of the mental l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…This process is referred to as switching. Thus, response patterns in semantic fluency tasks reflect lexical organization and lexical retrieval processes (e.g., Marshall et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This process is referred to as switching. Thus, response patterns in semantic fluency tasks reflect lexical organization and lexical retrieval processes (e.g., Marshall et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Gershkoff-Stowe and Hahn (2007), children with smaller vocabularies perform poorer on word learning tasks, and DHH children often have lower vocabulary than their hearing peers (e.g. Blamey, 2003;Coppens et al, 2012;Marshall et al, 2018). Connecting such measurements to results of a spoken word learning task with manual stimuli would be interesting to include in future research.…”
Section: Discussionmentioning
confidence: 87%
“…For children to acquire the words of a spoken language, however, auditory access is vital. Children who are deaf/hard-of-hearing (DHH) have limited access to spoken language even when they use hearing aids (HAs) and/or cochlear implants (CIs), and this limited access may impede their spoken vocabulary development (Blamey, 2003; Marshall et al, 2018). Indeed, upon entering primary school, many DHH children have smaller vocabularies in their spoken language than their hearing peers (Coppens et al, 2012; Hayes et al, 2009), and some never catch up (Convertino et al, 2014; Sarchet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This has important implications for d/Dhh readers in constructing a more thorough understanding of their skills and needs. The widespread difficulties that many d/Dhh individuals have with English fluency (Anderson, ; Blamey & Sarant, ; Marshall et al, ; Sarant, Holt, Dowell, Rickards, & Blamey, ) suggest some potential parallels with readers who are English Language Learners. Research on dialect and bilingual strategies across diverse hearing populations has demonstrated that readers’ miscues are schema‐driven to include culture and dialect.…”
Section: Theoretical Foundations Of Miscue Analysismentioning
confidence: 99%